2009
DOI: 10.1007/s11011-009-9134-9
|View full text |Cite
|
Sign up to set email alerts
|

NAD metabolism in HPRT-deficient mice

Abstract: The activity of hypoxanthine-guanine phosphoribosyltransferase (HPRT) is virtually absent in Lesch-Nyhan disease (LND), an X-linked genetic disorder characterized by uric acid accumulation and neurodevelopmental dysfunction. The biochemical basis for the neurological and behavioral abnormalities have not yet been completely explained. Prior studies of cells from affected patients have shown abnormalities of NAD metabolism. In the current studies, NAD metabolism was evaluated in HPRT gene knock-out mice. NAD co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 25 publications
0
8
0
Order By: Relevance
“…A pharmacological model, the 6-hydroxydopamine-treated rat, in which catecholamine-containing neurons were destroyed, showed self-injurious behavior in response to DOPA-agonist administration, supporting the connection between selfinjurious behaviour and DA deficit [109]. A genetic model, the HPRT-knockout mouse also mentioned above [103], did not show neurobehavioral alterations, but presented an agerelated decreased content of DA in the brain [110]. DA deficit has been confirmed in various HPRT-deficient cell cultures developed to study the effects of the enzyme deficit and of purine alterations [107,111,112].…”
Section: Hypoxanthine-guanine Phosphoribo-syltransferase Deficiency Amentioning
confidence: 89%
See 1 more Smart Citation
“…A pharmacological model, the 6-hydroxydopamine-treated rat, in which catecholamine-containing neurons were destroyed, showed self-injurious behavior in response to DOPA-agonist administration, supporting the connection between selfinjurious behaviour and DA deficit [109]. A genetic model, the HPRT-knockout mouse also mentioned above [103], did not show neurobehavioral alterations, but presented an agerelated decreased content of DA in the brain [110]. DA deficit has been confirmed in various HPRT-deficient cell cultures developed to study the effects of the enzyme deficit and of purine alterations [107,111,112].…”
Section: Hypoxanthine-guanine Phosphoribo-syltransferase Deficiency Amentioning
confidence: 89%
“…By contrast decreased NAD, ATP and GTP concentrations and increased NAD production from nicotinic acid were measured in LNS fibroblasts [93]. NAD concentration and enzyme activities committed to its metabolism were found to be significantly increased in liver, but not in brain or blood of HPRT-knockout mice, animal models of LNS [103]. Together these findings suggest that disturbed pyridine metabolism accompanies the purine perturbation associated to HPRT deficiency in different cell types and lead to hypothesize the possible involvement of NAD and PARP in LNS neurological symptoms.…”
Section: Hypoxanthine-guanine Phosphoribo-syltransferase Deficiency Amentioning
confidence: 91%
“…A pharmacological model, the 6-hydroxydopamine-treated rat, in which catecholaminecontaining neurons were destroyed, showed self-injurious behavior in response to DOPA-agonist administration, supporting the connection between self-injurious behaviour and DA defi cit [60]. The already mentioned genetic model (the HPRT-knockout mouse) [55] did not show neurobehavioral alterations but presented an age-related decreased content of DA in the brain [61]. Various HPRT-defi cient cell cultures were developed to study the effects of the enzyme defi cit and of purine alterations [62,63,64] and confi rmed DA defi cit.…”
Section: Investigations On the Pathogenesis Of Neurological And Behavmentioning
confidence: 79%
“…By contrast decreased NAD, ATP and GTP concentrations and increased NAD production from nicotinic acid were measured in LND fi broblasts [38]. NAD concentration and related enzyme activities were found to be signifi cantly increased in liver, but not in brain or blood, of HPRT-knockout mice, animal models of LND [55]. Together these fi ndings suggested that disturbed pyridine metabolism may accompany the purine perturbation associated to HPRT defi ciency in different cell types and possibly be involved in LND neurological symptoms.…”
Section: Investigations On the Pathogenesis Of Neurological And Behavmentioning
confidence: 94%
“…In vitro, cells tend to increase the de novo synthesis to compensate for a recycling deficit, a situation that is not physiologically possible in the brain, where the de novo pathway enzymes are only poorly active (12). This highlights the intrinsic ability of different cell types to mobilize alternative energy supplies to cope with bioenergetics stress -a property termed "metabolic flexibility" (34,35). However, 1 caveat of our study is that it mainly relied upon morphological observations of the neuronal network.…”
Section: Discussionmentioning
confidence: 99%